The experience of living with knee osteoarthritis: exploring illness and treatment beliefs through thematic analysis - Pouli, Nektaria; das Nair, Roshan; Lincoln, Nadina; Walsh, David A. (Taylor & Francis, 2013)
Purpose: Knee osteoarthritis (OA) is a major cause of disability in older adults. However, there is limited research on the daily experience of living with knee OA. We aimed to offer insight into the beliefs of patients with knee OA about their illness and treatment.